2017
DOI: 10.5935/2359-4802.20170059
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Metabolic Syndrome in the Elderly: A Review

Abstract: The article aimed to critically analyse studies which evaluated the capacity of anthropometric and clinical indicators to predict MetS in the elderly. Bibliographical research was performed using the electronic databasese Medline/PubMed, LILACS e SciELO , references from selected articles and contact with several authors. Twenty one articles involving anthropometric and clinical indicators in the elderly were analysed, using different MS criteria. Fourteen studies report anthropometric indicators, being the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
5
7
0
Order By: Relevance
“…However, this results in the insulin resistance of the muscle and the liver caused by reduced insulin production by the pancreatic β-cell [ 42 ] giving rise to metabolic complications. Body mass index in both males and females was not the best indicator of MetS, similar findings were reported by [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Several studies have indicated that, although BMI is extensively used in a population to assess overall body weight it has limitations that it cannot differentiate between fat mass and fat-free mass [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ,…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, this results in the insulin resistance of the muscle and the liver caused by reduced insulin production by the pancreatic β-cell [ 42 ] giving rise to metabolic complications. Body mass index in both males and females was not the best indicator of MetS, similar findings were reported by [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Several studies have indicated that, although BMI is extensively used in a population to assess overall body weight it has limitations that it cannot differentiate between fat mass and fat-free mass [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ,…”
Section: Discussionsupporting
confidence: 87%
“…In the general population of Ellisras, WC, WHtR and NC were the best indices to determine MetS than BMI. Similar results were reported by [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] although, the studies used different sample size, had different ethnicity and used different variables in the methodology. The use of obesity indices in these population can help screen and diagnose MetS as well as identify individuals at risk of health complications.…”
Section: Discussionsupporting
confidence: 86%
“…The growth in the number of people with diseases associated to the weight excess make the experts consider obesity a disease with serious problems to public health [1]. The excess of adipose tissue with abdominal distribution, has been associated to the growth of incidence of several kinds of diseases especially the ones related to the metabolic syndrome [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still no consensus about which adiposity indicator is the best predictor of cardiovascular events resulting from body fat accumulation within this age group [5,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%